Estimation of the remaining periodontal ligament from attachment-level measurements - T. Yamamoto (journal of clinical periodontology, 2006)
Aim: Accurate assessment of the remaining area of periodontal attachment assists in determining the prognosis of a tooth. The aim of this study was to determine formulae to estimate the remaining area of periodontal attachment from attachment-level measures. Materials and Methods: Roots of 30 extracted teeth of each tooth type were coated with vinyl acetate solution and a-cyanoacrylate monomer to produce a membrane. The membrane was removed after guidelines were drawn to simulate various attachment levels. The root surface area on the apical side of each simulated attachment level was measured using image analysis software. The net or percent root surface area and corresponding attachment level data were fitted to a linear, quadratic, cubic, and exponential functions and a growth curve. Results: The linear function provided the most appropriate fit for the data. For net root surface area, a steeper slope was evident for tooth types with a larger mean total root surface area. For percent root surface area, a steeper slope was evident for tooth types with a shorter root length. Conclusions: A linear function provides the most appropriate formula for estimation of the remaining area of periodontal attachment based on the attachment-level measurement.